Model Utilisasi Dan Visualisasi Resource Menggunakan Prometheus Dan Grafana Untuk Pengelolaan Server Di Universitas Udayana - Putra, Agus Permana; Sukadarmika, Gede; Wiharta, Dewa Made (Majalah Ilmiah Teknologi Elektro, 2024)
Monitoring utilization server which refers to the use of server resources such as CPU, memory and storage is important in managing Information Technology (IT) infrastructure by network administrators in an effort to help maximize server performance, identify performance constraints and make decisions to increase efficiency servers. Monitoring is done by checking resource usage one by one on the server to find out which server resources are running. However, the more servers there are, the more time it takes to monitor so that it can interfere with the performance of network administrators. To make it easier for network administrators to monitor, researchers created a resource utilization and visualization model using Prometheus and Graphana which can display server resources without having to check directly on the server you want to monitor. The final result of the research produced a model that can visualize server resources in a dashboard without the need to check the servers one by one so that it helps network administrators work to monitor server resource usage.